Mark Bittman's kitchen matrix : more than 700 simple recipes and techniques to mix and match for endless possibilities. - Bittman, Mark (Pam Krauss Books, 2015)
"Bestselling author Mark Bittman anthologizes his popular Matrix series in a boldly graphic new cookbook that emphasizes creativity, improvisation, and simplicity as the keys to varied cooking. Mark Bittman's Kitchen Matrix is a collection of Bittman's Matrix pieces, the most popular feature of his "Eat" column for the New York Times Magazine. Each matrix presents one ingredient or technique served up 12 ways, showing how a simple alteration of a basic recipe can yield wildly different results"--